2021
DOI: 10.4251/wjgo.v13.i10.1229
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in cholangiocarcinoma: An autophagy-based treatment strategy

Abstract: Cholangiocarcinomas (CCAs) are diverse biliary epithelial tumours involving the intrahepatic, perihilar and distal parts of the biliary tree. The three entirely variable entities have distinct epidemiology, molecular characteristics, prognosis and strategy for clinical management. However, many cholangiocarcinoma tumor-cells appear to be resistant to current chemotherapeutic agents. The role of autophagy and the therapeutic value of autophagy-based therapy are largely unknown in CCA. The multistep nature of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 118 publications
0
16
0
Order By: Relevance
“…Some noteworthy rapalogs are everolimus, as well as temsirolimus, while deforolimus is a rapamycin analog, which activates the autophagy mechanism [84]. It is reported that the addition of Paclitaxel inEverolimus therapy has a significant suppressive effect on endometrial cancer cell progression [85]. There is a notable effect of Rapamycin as an anti-cancer treatment, which includes the activation of the autophagy pathway, the enhancement of radiationtherapy's effect on lung cancer cells of the -A549 type, and it also influences the DNA-repair process [86].…”
Section: Autophagy Enhancer Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some noteworthy rapalogs are everolimus, as well as temsirolimus, while deforolimus is a rapamycin analog, which activates the autophagy mechanism [84]. It is reported that the addition of Paclitaxel inEverolimus therapy has a significant suppressive effect on endometrial cancer cell progression [85]. There is a notable effect of Rapamycin as an anti-cancer treatment, which includes the activation of the autophagy pathway, the enhancement of radiationtherapy's effect on lung cancer cells of the -A549 type, and it also influences the DNA-repair process [86].…”
Section: Autophagy Enhancer Agentsmentioning
confidence: 99%
“…For breast malignancy, in the absence of mutant BRCA1 gene, metformin can be included in therapeutic schemes with spautin-1, which constitutes an autophagy suppressor, resulting in an altered mitochondrial functional state and inducing a notable reduction incancer cell survival and progression [88,90]. Furthermore, significant autophagy suppressors are mTOR inhibitors, such as alkaloids [90,91], including cepharanthine, liensinine, andisoliensinine [85], while they induce phosphorylation of the AMPK pathway. The above autophagy activators demonstrate great results in cases of resistant apoptosis in Mouse Embryonic Fibroblasts (MEFs) [92].…”
Section: Autophagy Enhancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In western countries is closely associated with chronic inflammation of the biliary tract, such as primary sclerosing cholangitis (PSC), biliary lithiasis, metabolic diseases, as well as chronic hepatic inflammatory diseases, including viral hepatitis B and C, NASH, mainly for intrahepatic cholangiocarcinogenesis. In Eastern countries, two well-demonstrated risks factor is a parasitic infection with larvae of Opisthorchis viverrini, and Clonorchissinesis via food consumption, as well as exposure to aflatoxins [ 7 , 8 ], which is also associated with HCC development. There is a notable association of anatomical sub-entities including, FGFR gene fusions, mutant IDH1/2, ARID1A, and BRAF genes in intrahepatic CCAs (iCCAs), while for extrahepatic tumors mutations in ELF3, IDH1/2, as well as PRKACA/B and FGFER fusions, while, TP53 and KRAS mutations are also reported for both subtypes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested autophagy plays an important role in the energy balance of cancer cells and may regulate the survival mechanism of cancer cells as a tumor promoter or tumor suppressor, and its intervention has become an effective strategy for cancer treatment [14,15]. Moreover, autophagy induction or autophagy inhibition has been used for the treatment of CCA in clinical studies, indicating that autophagy is an effective target for CCA therapy [16,17]. However, the molecular basis of the relationship between autophagy and I-125 seed radiation in CCA has not yet been further studied, to the best of our knowledge.…”
mentioning
confidence: 99%